An Enhanced Safety Algorithm for Network QoS Multicast Routing Optimization - Liu Wei; Cui Yong-Feng; Li Ya (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the traditional QoS multicast network routing algorithm, when the node encounters abnormal traffic network data, the node data overflows. The current protocol is lack of directional guidance for overflow, which causes abnormal data jitter and disorder, the data path planning of traditional Qos protocol blocked and network delay. In order to solve this problem, this paper presents an enhanced safety algorithm for QoS multicast network routing optimization. The constraint relationship between security level of input parameters of network service request and trust level of network service is set, in order to judge and screen the traffic overflow nodes generated by abnormal operation. Then filtered set of network services is used to construct a multi-path network services digraph and converts it into web services selection tree in use of pointing relationship between sub-services. Finally, it sorts the paths and according to the size of Qos path selects the optimal one to carry out through tracing method. Simulation results show the new algorithm has optimum network quality of service and lower complexity. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4245